Pulse generation in erbium-doped fiber laser using a passive technique / Muhamad Burhan Shah Sabran - Muhamad Burhan Shah, Sabran (2016)

(untitled)
Various new pulsed fiber lasers operating in single-wavelength and dualwavelength modes are proposed and demonstrated using a low cost and simple approach. At first, a stable passive Q-switched fiber laser operating at 1543.5 nm is demonstrated using a double-clad Erbium-Ytterbium co-doped fiber (EYDF) as the gain medium in conjunction with nonlinear polarization rotation (NPR) technique. Polarization dependent isolator is used in conjunction with a highly nonlinear EYDF to induce intensity dependent loss in a sufficiently-high loss ring cavity to achieve Qswitched operation. At 980 nm multimode pump power of 500 mW, the EYDF laser (EYDFL) generates an optical pulse train with a repetition rate of 46.95 kHz, pulse width of 5.3 μs and pulse energy of 75.6 nJ. A dual-wavelength EYDFL is also demonstrated using the similar NPR technique. Besides, the NPR, graphene oxide (GO) could also be used as a saturable absorber (SA) in fiber laser cavity for pulse generation. In this work, two different Q-switched Erbium-doped fiber lasers (EDFLs) are demonstrated using a GO paper as a SA. A stable and self-starting Q-switched operation was achieved at 1534.4 nm by using a 0.8 m long Erbium-doped fiber (EDF) as gain medium. The pulse repetition rate changes from 14.3 to 31.5 kHz while the corresponding pulse width decreases from 32.8 to 13.8 μs as the pump power is increased from 22.0 to 50.5 mW. A narrow spacing dual-wavelength Q-switched EDFL can also be realized by including a photonics crystal fiber and a tunable Bragg filter in the setup. Finally, a mode-locked EDFL is demonstrated by using the similar GO paper SA. A GO SA based mode-locked EDFL can be realized by using a 1.6 m long EDF in conjunction with 1480 nm pumping. The laser generates a soliton pulse train with a repetition rate of 15.62 MHz and pulse width of 870 fs. These results show that the proposed GO paper is a suitable SA component for generating both Q-switched and mode-locked EDFL operating in 1.5 micron wavelength region.